Hedonisme Berdasarkan Perspektif Agama Islam - Ninil Elfira; Mutia Azzahra; Cinta Praseptia; Olivia S. Abbas; Alya Alya; Inda Maharani Toding (Institut Agama Islam Sumatera Barat, 2024)
Hedonism is a philosophical view that emphasizes that achieving happiness through physical and material pleasure is the most important aspect of human life. This phenomenon is quite worrying among adolescents because it can encourage them to engage in risky behavior such as substance abuse, free sex, and excessive lifestyles. Hedonism is contrary to Islamic teachings which emphasize the balance between worldly and hereafter needs. This study aims to examine the factors causing adolescent hedonism, its impacts, and the solutions offered by Islam. With a literature approach, the study explores driving factors such as the search for self-identity, peer influence, lack of parental supervision, and media influence. The impacts of hedonism include consumer behavior, decreased academic achievement, moral degradation, and psychological problems. Islam offers a solution by strengthening faith, being grateful, being content, doing good deeds, being careful in socializing, living simply, and focusing on work to counteract adolescent hedonism.